2021
DOI: 10.9778/cmajo.20200190
|View full text |Cite|
|
Sign up to set email alerts
|

Buprenorphine–naloxone practice and attitudes in 22 Canadian emergency physician groups: a cross-sectional survey

Abstract: E mergency departments (EDs) play a critical role in delivering services to people with opioid use disorder (OUD). 1,2 Emergency department physicians have not always been uniformly willing and able to provide these services, 3 even though patients with OUD visit EDs frequently 4 and most people who die of opioid overdose have visited an ED in the year preceding death. 5 For those ED and emergency medical services patients who survive an overdose, the subsequent 1-year mortality rate is 5%-15%. [6][7][8] In bo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
15
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(17 citation statements)
references
References 34 publications
(45 reference statements)
2
15
0
Order By: Relevance
“…This is the first study to identify barriers and facilitators to implementing opioid safety initiatives (opioid prescribing, initiation of M‐OUD, and naloxone distribution) in VA ED/UCC settings. Similar to research conducted in other settings, 6–9 we have identified barriers to the implementation of ED‐based opioid safety initiatives which include provider perceptions that OUD care is outside of the scope of the ED, lack of education (for both providers and patients), difficulty obtaining follow‐up care, and the stigma associated with substance use disorder diagnoses and treatment. The facilitators to implementing these ED‐based opioid safety initiatives are similar in some ways: culture change to destigmatize caring for patients with substance use disorder, increased education and awareness (for providers and patients), protocolized local pathways for diagnosis, treatment and follow‐up, use of technology, and advocacy from national organizations to reduce regulatory obstacles (e.g., X‐waiver requirement).…”
Section: Discussionmentioning
confidence: 87%
See 2 more Smart Citations
“…This is the first study to identify barriers and facilitators to implementing opioid safety initiatives (opioid prescribing, initiation of M‐OUD, and naloxone distribution) in VA ED/UCC settings. Similar to research conducted in other settings, 6–9 we have identified barriers to the implementation of ED‐based opioid safety initiatives which include provider perceptions that OUD care is outside of the scope of the ED, lack of education (for both providers and patients), difficulty obtaining follow‐up care, and the stigma associated with substance use disorder diagnoses and treatment. The facilitators to implementing these ED‐based opioid safety initiatives are similar in some ways: culture change to destigmatize caring for patients with substance use disorder, increased education and awareness (for providers and patients), protocolized local pathways for diagnosis, treatment and follow‐up, use of technology, and advocacy from national organizations to reduce regulatory obstacles (e.g., X‐waiver requirement).…”
Section: Discussionmentioning
confidence: 87%
“…Similar to research conducted in other settings, [6][7][8][9] we have iden- This shift in the care journey for patients with OUD will require multidisciplinary approaches to education and training, 19 addressing provider biases and stigma, 20 and using whole health approaches (including complementary and integrative medicine) 21 to change the current treatment paradigm that often focuses on physical ailments and not addressing underlying addiction and mental health concerns. Currently, educational efforts, in part, focus on regulatory requirements for X-waiver training, 5 national and federal policy statements, [3][4][5] and guidelines for care.…”
Section: Discussionmentioning
confidence: 88%
See 1 more Smart Citation
“…We conducted a nationwide paper and electronic survey of physicians at rural and urban EDs in 6 provinces from December 1, 2018 to November 30, 2019. We previously published full survey methodology [ 8 ], in accordance with the CHERRIES reporting checklist ( https://www.equator-network.org ). The questionnaire in English and French included items adapted from previously validated Likert scale questions on attitudes, as well as questions on individual and site-specific characteristics (questionnaire: S1 Appendix ).…”
Section: Methodsmentioning
confidence: 99%
“…Because engaging patients in addictions treatment is challenging, ED providers do not capitalize on every opportunity to initiate BUP. Although two-thirds of emergency physicians are willing to initiate BUP, only one-quarter report doing so at least once a month [ 8 ]. While US-based research has identified relevant individual- and site-level predictors of BUP initiation in the ED [ 9 , 10 ], Canadian data are lacking.…”
Section: Introductionmentioning
confidence: 99%